I would to solve the Diophantine equation $2x^4 - 2y^4 = z^2$ by descent. This is an exercise from Carmichael Diophantine Analysis but I cannot do it.

Since the LHS is even $2|z$, let $z = 2z'$ and divide both sides by $2$ to get $$(x-y)(x+y)(x^2+y^2)=2z'^2.$$ Congruence conditions tell us that either x and y are both odd or both even, that tells us both sides are a multiple of $8$ so let $z' = 2z''$ and we have $$\frac{x-y}{2}\frac{x+y}{2}\frac{x^2+y^2}{2}=z''^2.$$ The problem now is I don't know if these numbers on the LHS are coprime so I can't claim they are all squares. I don't see any way to continue so maybe I took a wrong turn earlier.

Any hints about how to deal with this equation?


If $p$ is a prime and it divides both $x$ and $y$, then it divides $z$: if $p$ is odd, then $p^4|z^2$; if $p=2$, then $32|z^2$. Either way, you can factor out the common prime from all of $x$, $y$, and $z$.

Thus, we may assume that $\gcd(x,y)=1$. Since you also know that $x\equiv y\pmod{2}$, you can reduce to the case where $x$ and $y$ are coprime and both odd.

Then $\gcd(x+y,x-y) = 2$, since any common divisor must divide $(x+y)+(x-y)=2x$ and $(x+y)-(x-y)=2y$, and the gcd of $2x$ and $2y$ is $2$. Therefore, $\frac{x-y}{2}$ and $\frac{x+y}{2}$ are coprime.

Any common divisor of $x-y$ and $x^2+y^2$ must divide $2x^2 = (x-y)(x+y) + (x^2+y^2)$, and must also divide $2y^2 = x^2+y^2 - (x-y)(x+y)$. Hence it must divide $\gcd(2x^2,2y^2) = 2$. Thus, $\gcd(x-y,x^2+y^2) = 2$. By the same argument, $\gcd(x+y,x^2+y^2) = 2$. This means that $\frac{x-y}{2}$ and $\frac {x^2+y^2}{2}$ are coprime, as are $\frac{x+y}{2}$ and $\frac{x^2+y^2}{2}$.

  • $\begingroup$ That means we can define a,b,c such that x-y = 2a^2, x+y = 2b^2 and x^2+y^2=2c^2. Adding and subtracting the first two gives x = a^2+b^2, y=b^2-a^2 which, substituting into the third equation proves that b^2 = c^2 so x+y=x^2+y^2.. does that imply that the complete solution of the equation is x=0 or 1 and y=0 or 1? $\endgroup$ – quanta Apr 1 '11 at 15:45
  • $\begingroup$ @quanta: I get $c^2 = a^4 + b^4$, not $b^2=c^2$. $\endgroup$ – Arturo Magidin Apr 1 '11 at 15:52
  • $\begingroup$ @Arturo, Thanks! I see my mistake. So we have instead a^4+b^4=c^2 -- it's not descent but it's reduction to a Diophantine equation I have already solved so I think that solves the equation! $\endgroup$ – quanta Apr 1 '11 at 15:54
  • $\begingroup$ @quanta: Yes. You have $a^4+b^4=c^2$ with $a$, $b$, and $c$ coprime, which has no nontrivial solutions. $\endgroup$ – Arturo Magidin Apr 1 '11 at 15:55
  • 1
    $\begingroup$ @quanta: No mismatch: there are only two solution with $x=y$ and $\gcd(x,y)=1$ (which was our first reduction), namely $x=y=\pm1$. Also, there was an implicit assumption that $z'\neq 0$: if $z'=0$, you cannot conclude that each of the factors is a square, just that one of them is equal to $0$ (which gives either $x=y$ or $x=-y$). $\endgroup$ – Arturo Magidin Apr 1 '11 at 18:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.